Konsep Takdir dalam Cerpen Berjudul Gus Jakfar Karya Ahmad Mustofa Bisri - Saputro, Andre Rifki Aji; Suroso, Eko (Proceedings Series on Social Sciences & Humanities, 2024)
One ongoing discussion that continues to be explored is the matter of destiny. This study stems from the relationship between literary works and the background of the author, which cannot be separated. The discussion focuses on the debate between two destiny doctrines regarding heaven and hell, as depicted in a short story titled "Gus Jakfar" by Ahmad Mustofa Bisri. The Qodariah destiny concept allows humans to have free will to choose between good and evil, while the Jabariah destiny concept regards everything as absolute from God, with humans having no will of their own. The aim of this study is to describe the destiny concepts found in the short story "Gus Jakfar" by Ahmad Mustofa Bisri.